Effects of RORγt overexpression on the murine central nervous system. Issue 1 (6th February 2021) - Sasaki, Tetsuya; Nagata, Rei; Takahashi, Satoru; Takei, Yosuke
Abstract: Objective: T helper 17 (Th17) cells are a subset of CD4 + T cells that produce interleukin (IL)‐17A. Recent studies showed that an increase in circulating IL‐17A causes cognitive dysfunction, although it is unknown how increased systemic IL‐17A affects brain function. Using transgenic mice overexpressing RORγt, a transcription factor essential for differentiation of Th17 cells (RORγt Tg mice), we examined changes in the brain caused by chronically increased IL‐17A resulting from excessive activation of Th17 cells. Results: RORγt Tg mice exhibited elevated Rorc and IL‐17A mRNA expression in the colon, as well as a chronic increase in circulating IL‐17A. We found that the immunoreactivity of Iba1 and density of microglia were lower in the dentate gyrus of RORγt Tg mice compared with wild‐type mice. However, GFAP + astrocytes were unchanged in the hippocampi of RORγt Tg mice. Levels of synaptic proteins were not significantly different between RORγt Tg and wild‐type mouse brains. In addition, novel object location test results indicated no difference in preference between these mice. Conclusion: Our findings indicate that a continuous increase of IL‐17A in response to RORγt overexpression resulted in decreased microglia activity in the dentate gyrus, but had only a subtle effect on murine hippocampal functions. Abstract : Using transgenic mice overexpressing RORγt, a transcription factor essential for differentiation of Th17 cells, we examined changes in the brain caused by chronically increased IL‐17A resulting from excessive activation of Th17 cells. RORγt Tg mice exhibited elevated Rorc and IL‐17A mRNA expression in the colon, as well as a chronic increase in circulating IL‐17A. Our findings indicate that a continuous increase of IL‐17A in response to RORγt overexpression resulted in decreased microglia activity in the dentate gyrus but had a subtle effect on murine hippocampal functions.